A fuzzy cognitive mapping-system dynamics approach to energy-change impacts on the sustainability of small and medium-sized enterprises - Pereira, I.; Ferreira, F.; Pereira, L.; Govindan, K.; Meidute-Kavaliauskiene, I.; Correia, R. (Journal of Cleaner Production, 2020)
Although large firms have already begun addressing energy efficiency issues and adopting “cleaner” types of energy, companies with fewer resources, such as small and medium-sized enterprises, are more reluctant to implemente these measures. Given that strategies leading to energy sustainability have become a key aspect of business competitiveness, decision makers in small and medium-sized enterprises could clearly benefit from a new approach that provides a better understanding of energy-change impacts on their business activities. The present study combined fuzzy cognitive mapping and the system dynamics approach to develop an informed, transparent model for use in analyses of energy-change effects on the sustainability of small and medium-sized enterprises. This dual methodology facilitated an examination of cause-and-effect relationships between decision criteria and the clarification of dynamic interactions between variables from a holistic, real-world perspective, thereby enriching the extant literature. The results of the proposed decision-support system were validated by two senior staff members of the Directorate for Energy Sustainability Services of Portugal’s Directorate General for Energy and Geology. The advantages, limitations, and implications of our constructivist, process-oriented framework for research and practice are also discussed.